CHRISTIAN VALUES IN OPERATIONAL FINANCING DECISIONS - Herdina, Ajeng Mira; Djazuli, Atim; Ratnawati, Kusuma (Universitas Brawijaya, Indonesia, 2018)
The purpose of this study is to describe the implementation of the Christian values which associated with the mechanism of operational financing decision. This study uses an interpretative approach with post-positivism paradigm, and the design of this study is a single case study. The object of this study is Providensia Adonay theological seminary in Batu City. The data obtained through interviews and documentation. The result of this study revealed that the application of Christian values as the base for operational financing decision mechanism in the theological seminary would create a decision of operational financing form that not only managed honestly and independently but also reflect the faith and reflect the concern of others. For further research, it is expected to carry out research that integrates religious values with financial management. Such integration will contribute to the development of theory from both parties.